2014
DOI: 10.1073/pnas.1416389112
|View full text |Cite|
|
Sign up to set email alerts
|

HLA ligandome analysis identifies the underlying specificities of spontaneous antileukemia immune responses in chronic lymphocytic leukemia (CLL)

Abstract: The breakthrough development of clinically effective immune checkpoint inhibitors illustrates the potential of T-cell-based immunotherapy to effectively treat malignancies. A remaining challenge is to increase and guide the specificities of anticancer immune responses, e.g., by therapeutic vaccination or by adoptive T-cell transfer. By analyzing the landscape of naturally presented HLA class I and II ligands of primary chronic lymphocytic leukemia (CLL), we delineated a novel category of tumor-associated T-cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
187
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 149 publications
(194 citation statements)
references
References 56 publications
5
187
0
Order By: Relevance
“…This is also corroborated by our previous studies which showed a high correlation of tumor association on the HLA ligandome level and immunogenicity in patients with chronic lymphatic leukemia. 47 In light of the clear in silico predictions of immunogenicity and the high cancer restriction of the identified HLA ligands, no additional T cell assays were carried out. Notably, predictions are in line with our previous studies, which demonstrated that non-mutated ligands, though derived from ubiquitous source proteins, are able to elicit T cell responses in cancer patients and therefore able to overcome central and peripheral tolerance if they are not detected on healthy PBMCs.…”
Section: Discussionmentioning
confidence: 99%
“…This is also corroborated by our previous studies which showed a high correlation of tumor association on the HLA ligandome level and immunogenicity in patients with chronic lymphatic leukemia. 47 In light of the clear in silico predictions of immunogenicity and the high cancer restriction of the identified HLA ligands, no additional T cell assays were carried out. Notably, predictions are in line with our previous studies, which demonstrated that non-mutated ligands, though derived from ubiquitous source proteins, are able to elicit T cell responses in cancer patients and therefore able to overcome central and peripheral tolerance if they are not detected on healthy PBMCs.…”
Section: Discussionmentioning
confidence: 99%
“…We also highlight selected biological applications and discuss important current technical limitations that need to be solved to accelerate the development of this field. The immunopeptidome is referred to as the collection of peptides associated with and presented by major histocompatibility complex (MHC) molecules (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). MHC-associated peptides are recognized by T lymphocytes that are in turn activated to eliminate abnormal cells such as pathogen-infected and cancer cells.…”
mentioning
confidence: 99%
“…Determining the absolute number of cell surface MHC molecules by flow cytometry and/or mass spectrometry is therefore an important initial step when establishing a new model system (28,29). On average, we noted from pertinent literature reports that the usage of at least ϳ5 ϫ 10 8 cells expressing ϳ2 ϫ 10 5 MHC molecules per cell was a minimum requirement for the exploration of cellular immunopeptidomes (3,4). Cell lines expressing low levels of endogenous class I molecules (e.g.…”
mentioning
confidence: 99%
“…However, considering the relatively low number of MHC-peptide complexes per cell and the potential MS detection limits, the majority of the data on self-, cancer, or pathogen MHC peptidomes come from immortalized cell lines (5)(6)(7)(8) or from models using cell lines engineered to secrete soluble MHC-bound peptide complexes (9)(10)(11), as both systems allow growth of high numbers of cells for peptide isolation. The improvements in peptide isolation and MS-based approaches led to the discovery of numerous MHC-I ligands presented by B cells or by patients' tumors (12)(13)(14) and the identification of virusderived MHC-bound peptides, including vaccinia virus and HIV presented by surface or soluble HLA (5,9,(15)(16)(17). These approaches identified self-and virus-derived noncanonical peptides and demonstrated that direct identification of peptides from infected cells will define the immunopeptidome relevant for the design of HIV immunogens.…”
mentioning
confidence: 99%